Pengaruh Karakteristik Sosiodemografi Kepala Rumah Tangga dan Anak Terhadap Kecenderungan Anak Terlibat dalam Pekerjaan Berbahaya di Sektor Pertanian: Analisis Data SAKERNAS - Sukma, Weni Lidya; Kadir, Kadir (Politeknik Statistika STIS, 2023)
In the agricultural sector, children may be involved in hazardous work that requires physical labor and long hours. Our study used SAKERNAS’s data conducted in August 2022 to examine the effect of both household heads’ and children’s sociodemographic characteristics on the child probability working in agricultural hazardous jobs. Our study confirms the importance of household heads' level in preventing children from working in agriculture and/engaging in hazardous job activities. The results of multinomial logistic regression using marginal effects pointed out that the education level of household heads have a positive impact on reducing the likelihood of child labor in agriculture and engagement of children in hazardous agricultural jobs. We also found the probability of children being child labour in agriculture and get involved in hazardous jobs is larger in female-head household compared to male-head household. In addition, increasing educational participation among children can also reduce the likelihood of child labor.